CONFINED SPACE PULSE GRAIN ENTRAPMENT & ENGULFMENT: A SERIES OF TWO FATAL ASPHYXIATIONS - Bodwal, Jatin; Chauhan , Mohit; Behera, Chittaranjan (Journal of Forensic Medicine and Toxicology, 2019)
Choking and traumatic asphyxiation as sub types of asphyxia causing fatality in two workers is presented. Different varieties of pulse grains were implicated in separate events of entrapment and engulfment in confined food pulse processing agricultural settings. Authors claim this as first case series describing pulse grain processing related occupational deaths. Death circumstances and autopsy findings are discussed along with review of literature.
Keywords: Confined space fatalities; grain/pulse silos; entrapment/engulfment; asphyxia